Heavy metal accumulation in Celery from Sarchnar and Kalar in Kurdistan of Iraq Region - Rashid, Khsraw A.; Mohammed, Zhino K. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Heavy metals pose risk to human health. The present study was carried out to assess levels of different heavy metals like lead, Copper, Chromium, Nickel and Iron, in celery irrigated with water from different sources. The results indicated a substantial build-up of heavy metals in vegetable irrigated with wastewater. The range of various metals in surface water mixed with wastewater-irrigated plants was 0.0005, 0.0003, 0.0086, 0.0006, 0.2106 mg/L for Pb, Cu, Cr, Ni and Fe respectively, in sarchnar location, and lowest value of these metals was determined in well water used for irrigation in kalar location and values are (0.0002, 0.0014, 0.0171, 0.0004 and 0.0020 mg/L) for Pb, Cu, Cr , Ni and Fe respectively. The highest levels of Fe detected in celery value 5.181and 3.983 mg/kg in Sarchnar and Kalar location, respectively. The present study highlights that both adults and children consuming vegetables grown in wastewater-irrigated soils ingest signiﬁcant amount of these metals. However, the values of these metals were below the recommended maximum tolerable levels. The regular monitoring of levels of these metals from efﬂuents and sewage, in vegetables and in other food materials is essential to prevent excessive build-up of these metals in the food chain.
Keywords: Environment; pollution; Heavy; metals; Human; toxicity; Irrigation; water; Water quality